Polyacrylamide backbones for polyvalent bioconjugates using "post-click" chemistry. Issue 38 (1st August 2016) - Nagao, M.; Kurebayashi, Y.; Seto, H.; Takahashi, T.; Suzuki, T.; Hoshino, Y.; Miura, Y.
Abstract : This paper reports the synthesis and application of acrylamide-type neoglycoconjugates interacting with practical targets. Abstract : This paper reports the synthesis and application of acrylamide-type neoglycoconjugates interacting with practical targets. Polymer backbones with acrylamide and acrylamide derivatives bearing alkyne groups were prepared using living radical polymerization. Oligosaccharides were introduced into the backbones using copper-catalysed azide–alkyne cycloaddition "post-click" chemistry.